Energy availability and macronutrient intake in elite male Gaelic football players - McGuire, A.; Warrington, G.; Doyle, L. (Science and Medicine in Football, 2023)
Evidence suggests that Gaelic football (GF) players do not meet the recommended energy intake (EI) levels and therefore may be at risk of low energy availability (LEA). This study examined energy availability (EA) in 20 elite male GF players. At two stages during a season (2019-2020), repeated measures of EI, exercise energy expenditure (EEE), EA and body composition were performed. Sixty-five percent reported with LEA [<30 kcal.kg Lean Body Mass (LBM)-1.day-1] at pre-season (PRE), with 70% at in-season (IN). Mean daily carbohydrate intake (PRE 3.2 ± 0.82 g.kg; IN 3.4 ± 0.79 g.kg) was below the recommended intake (5-7 g.kg) in 95% at PRE and 100% at IN. All consumed the recommended daily amount of protein (PRE 1.85 ± 0.57 g.kg; IN 1.87 ± 0.48 g.kg) and fat (PRE 1.23 ± 0.4 g.kg; IN 1.02 ± 0.3 g.kg). Significant correlations (P = 0.001) were reported between EA and carbohydrates (PRE r = 0.801; IN r = 0.714); protein (PRE r = 0.675; IN r = 0.769); fat (PRE r = 0.805; IN r = 0.733) and energy intake (PRE r = 0.960; IN r = 0.949). Twenty percent were at risk of disordered eating. This study suggests male elite GF players require education and interventions surrounding nutrition, in particular EA.